Malnutrizione associata a patologie, una problematica da risolvere - Eandi, Mario; Pradelli, Lorenzo; Palmo, Augusta (Farmeconomia. Health economics and therapeutic pathways, 2002)
Disease-related malnutrition, the most frequent cause of undernourishment in industrialized countries, appears to be highly prevalent among western patient populations, interesting up to 60% of the hospitalized and almost one fifth of the persons attending to the general medicine service. There are several reasons for this high prevalence, among which pathology-related causes, inadequate presentation of the meals in hospitals and institutions, and low recognition of nutritional problems by health professionals. Several studies have shown that undernourished patients have higher morbidity and mortality rates than the general population and suffer of more and more severe complications, leading to prolonged hospital stays and worse clinical outcomes. This determines a much higher Health costs, estimated in an English study as a yearly additional burden of over 7 billion £ for the National Heath Service. Nutritional interventions, such as the administration of oral supplements or enteral tube feeding, are capable to increase body mass index (BMI), that is considered the most reliable indicator of the nutritional status, muscle strength and overall psycho-physical performance, determining an improved quality of life and a reduced need for medical assistance. These functional improvements go alongside with better clinical outcomes, as shown by a reduced mortality rate, shorter hospital stays and lower incidence of complications observed after supplementation. Studies that have analyzed the economical impact of nutritional supplementation in terms of cost-benefit have shown that the cost of enteral nutritional interventions is almost negligible when compared to the associated savings in the production of the health service, mainly determined by lower hospitalization rates, shorter hospital stays, reduced costs for the treatment of complications and for the consultation of specialists. Greater awareness of the health professionals and more encouraging health policies toward nutritional interventions are required to reduce the clinical and economical impact of this unnecessarily wide-spread condition.